1989
DOI: 10.1111/j.1399-3054.1989.tb06219.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen toxicity and superoxide dismutase as an antioxidant in physiological stress

Abstract: Although oxygen is vital for all aerobic life forms, excessive levels of oxygen free radical production can lead to potentially lethal oxidative reactions. The role of superoxide dismutase is examined as an integral part of the defence against oxidative injury resulting from various physiological stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(45 citation statements)
references
References 21 publications
0
44
0
1
Order By: Relevance
“…In addition to proteolysis, ROS can damage lipids, terpenoids, carbohydrates, and nucleic acids (Monk et al 1989;Baier and Dietz 1998). The capacity to scavenge ROS and to reduce their damaging effects is important for stress-tolerance (Tsugane et al 1999).…”
Section: Detoxificationmentioning
confidence: 99%
“…In addition to proteolysis, ROS can damage lipids, terpenoids, carbohydrates, and nucleic acids (Monk et al 1989;Baier and Dietz 1998). The capacity to scavenge ROS and to reduce their damaging effects is important for stress-tolerance (Tsugane et al 1999).…”
Section: Detoxificationmentioning
confidence: 99%
“…Increase in the activity of antioxidant enzymes in response to various environmental stresses has also been reported in various studies (Elstner 1986, Bowler et al 1992, Sairam and Srivastava 2001, Sairam et al 2000. In Iris pseudacorus a 14-fold increase in SOD was observed during a reoxygenation period (Monk et al 1989). Van Toai and Bolles (1991) demonstrated that high SOD activity may contribute to flooding tolerance by improving detoxification of superoxide upon re-admission of oxygen.…”
Section: Introductionmentioning
confidence: 97%
“…Reactive oxygen species (ROS), such as hydrogen peroxide, superoxide anion, and hydroxyl radicals, damage cell membrane components, degrade polysaccharides, and denature enzymes (Halliwell et al 1988; Monk et al 1989). Plants have developed very efficient antioxidant systems to scavenge ROS to provide protection against oxidative stress (Allen 1995).…”
Section: Introductionmentioning
confidence: 99%